Feasibility of measuring fusional vergence amplitudes objectively - Rovira-Gay, Cristina; Mestre, Clara; Argiles, Marc; Vinuela-Navarro, Valldeflors; Pujol, Jaume (PloS one, 2023)
Two tests to measure fusional vergence amplitudes objectively were developed and validated against the two conventional clinical tests. Forty-nine adults participated in the study. Participants’ negative (BI, base in) and positive (BO, base out) fusional vergence amplitudes at near were measured objectively in an haploscopic set-up by recording eye movements with an EyeLink 1000 Plus (SR Research). Stimulus disparity changed in steps or smoothly mimicking a prim bar and a Risley prism, respectively. Break and recovery points were determined offline using a custom Matlab algorithm for the analysis of eye movements. Fusional vergence amplitudes were also measured with two clinical tests using a Risley prism and a prism bar. A better agreement between tests was found for the measurement of BI than for BO fusional vergence amplitudes. The means ± SD of the differences between the BI break and recovery points measured with the two objective tests were -1.74 ± 3.35 PD and -1.97 ± 2.60 PD, respectively, which were comparable to those obtained for the subjective tests. For the BO break and recovery points, although the means of the differences between the two objective tests were small, high variability between subjects was found (0.31 ± 6.44 PD and -2.84 ± 7.01 PD, respectively). This study showed the feasibility to measure fusional vergence amplitudes objectively and overcome limitations of the conventional subjective tests. However, these tests cannot be used interchangeably due to their poor agreement.